Effects of short-term training using Powercranks on cardiovascular fitness and cycling efficiency - Luttrell, M. D.; Potteiger, J. A. (The Journal of Strength and Conditioning Research, 2003)
Powercranks use a specially designed clutch to promote independent pedal work by each leg during cycling. We examined the effects of 6 wk of training on cyclists using Powercranks (n = 6) or normal cranks (n = 6) on maximal oxygen consumption (O2max) and anaerobic threshold (AT) during a graded exercise test (GXT), and heart rate (HR), oxygen consumption (O2), respiratory exchange ratio (RER), and gross efficiency (GE) during a 1-hour submaximal ride at a constant load. Subjects trained at 70% of O2max for 1 h·d1, 3 d·wk1, for 6 weeks. The GXT and 1-hour submaximal ride were performed using normal cranks pretraining and posttraining. The 1-hour submaximal ride was performed at an intensity equal to approximately 69% of pretraining O2max with O2, RER, GE, and HR determined at 15-minute intervals during the ride. No differences were observed between or within groups for O2max or AT during the GXT. The Powercranks group had significantly higher GE values than the normal cranks group (23.6 ± 1.3% versus 21.3 ± 1.7%, and 23.9 ± 1.4% versus 21.0 ± 1.9% at 45 and 60 min, respectively), and significantly lower HR at 30, 45, and 60 minutes and O2 at 45 and 60 minutes during the 1-hour submaximal ride posttraining. It appears that 6 weeks of training with Powercranks induced physiological adaptations that reduced energy expenditure during a 1-hour submaximal ride.